Deformation in a Three-Phase-Lag Model of Orthotropic Thermoviscoelastic Material (Global Journal of Science Frontier Research, 2018)
The present paper is aimed at studying the effect of viscosity on thermoelastic interactions in three-phase-lag model of a homogeneous thermally conducting orthotropic material whose surface is subjected to thermal excitations. The governing equations are solved by applying Laplace and Fourier transforms technique. Eigen value approach is used to obtain the expressions for the variables considered. Numerical computations are performed for a specific material and result obtained are represented graphically for temperature gradient boundary. Comparsions are made with in the theory in the presence and absence of viscosity effect.
Keywords: generalized thermo elasticity; orthotropic material; relaxation time; laplace and fourier transforms; instantaneous loading; continuous loading